PERSEPSI PASIEN PREOPERATIF TERHADAP PERILAKU CARING PERAWAT - Agusriansa ' '; Erwin ' '; Nurul ' Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Caring behaviour is an emotional attitude in giving nursing services,caring behaviour is moral commitment to protect, increase human dignity and the core of nursing care that distinguish a nurse with another profession.This study using descriptive survey method, that tries to analyse the caring behavior received by patients who will undergo surgery in the Dahlia room Arifin Achmad Hospital. The samples in this research is 51 patients who will undergo surgery taken by applying puspossive sampling method. The instrument used inthis research is Caring Behaviour Assessment ( CBA ) that has been modified by researchers and passing through validity and reliability test.The results of research discuss characteristics concerning of age, sex, long treated and respondents education.The result showed all nurses has given treatment with based on caring . As many as 45.1 % of the respondents indicated the caring behaviour of nurse are categorized as high, 54,9 % of respondents said caring behavior of nurse have included to medium category.Caring behavior divided into 3 subvariabel consist of affective behavior, instrumental behavior, and preoperatif care.Based on research results, Affective behaviour received the highest valuation from the respondents.Increased knowledge of caring behavior by nurses be the main advice to create optimal nursing care. Keyword : Caring Behaviour, Nursing, Preoperative Patient